2014
DOI: 10.1160/th14-02-0126
|View full text |Cite
|
Sign up to set email alerts
|

The role of platelets in sepsis

Abstract: Platelets are small circulating anucleate cells that are of crucial importance in haemostasis. Over the last decade, it has become increasingly clear that platelets play an important role in inflammation and can influence both innate and adaptive immunity. Sepsis is a potentially lethal condition caused by detrimental host response to an invading pathogen. Dysbalanced immune response and activation of the coagulation system during sepsis are fundamental events leading to sepsis complications and organ failure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
129
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(131 citation statements)
references
References 122 publications
(156 reference statements)
2
129
0
Order By: Relevance
“…Due to their high number in the circulatory system and the expression of immune receptors, platelets can be considered as the first responding innate immune cells towards invading bacteria. Platelet activation is a common observation in septic patients, and it has therefore been suggested as biomarker for the development of sepsis [88]. …”
Section: Pneumococcal and Staphylococcal Interactions With Soluble Plmentioning
confidence: 99%
“…Due to their high number in the circulatory system and the expression of immune receptors, platelets can be considered as the first responding innate immune cells towards invading bacteria. Platelet activation is a common observation in septic patients, and it has therefore been suggested as biomarker for the development of sepsis [88]. …”
Section: Pneumococcal and Staphylococcal Interactions With Soluble Plmentioning
confidence: 99%
“…(36,37) In septic patients thrombocytopenia is due to platelet consumption because of exacerbated activation of the coagulation system, also leading to coagulation factor consumption. Boechat et al proved that a platelet count lower than 150x10³/ uL was significantly correlated with mortality in patients with sepsis and that normalization of platelet count improved prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…PF4 binds to bacteria and reduces the lag time for aggregation. Other platelet receptors that mediate platelet-bacterial interactions are GPIbα, PAR1, and TLRs [8]. It has been suggested that platelets, through the expression of TLR4, act as a barometer for systemic infection [17] and function as sensors of pathogens.…”
Section: Platelet Activation and Response In Sepsismentioning
confidence: 99%
“…During sepsis, an increase in circulating platelet-neutrophil complexes is observed. These complexes initially rise in the beginning of sepsis and decrease when MODS (multiple organ dysfunction syndrome) occurs indicating peripheral sequestration [8].…”
Section: Platelets and Netsmentioning
confidence: 99%
See 1 more Smart Citation